Control of DFIG Stator Voltage on Autonomous Micro Hydro Power Plant - Feri Yusivar; Nanda Avianto Wicaksono; Aries Subiantoro; Ridwan Gunawan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
An autonomous micro hydro power plant was proposed to utilize the small hydro power potency as a run-of-river. It consisted of a PMSG, a DFIG, and a converter and should be operated in the off-grid configuration. In a previous research, the DFIG stator voltages couldn’t be controlled. In this paper, the novel control algorithm that is able to maintain the DFIG stator voltages of the autonomous micro hydro power plant in the off-grid configuration is proposed. The control algorithm was proposed to use the actual DFIG stator voltages and currents as feedback signals. The controller was tested by varying three input signals, i.e. the DC-link voltage, the DFIG stator voltage reference, and the external stator load which simulated the off-grid configuration. The result of the simulation showed that the DFIG stator voltages could be controlled and were always in accordance with the reference.